BRCA1 and BRCA2 variants identified in patients with a personal/familial history of hereditary breast/ovarian cancers and other hereditary cancer syndromes: challenges related with variants of uncertain significance - Rodrigues, Pedro (2021)
Introduction: Screening for BRCA1 and BRCA2 variants (Vs) in patients with Hereditary Breast/Ovarian Cancer (HBOC) or other Hereditary Cancer Syndromes (HCS) is performed using next-generation sequencing (NGS), allowing detection of a high number and types of Vs. The growing use of PARP inhibitors (PARPi) in the treatment of patients with homologous recombination-deficient tumors contributes to an increasing number of patients being screened for BRCA Vs even when family history of HBOC/HCS is absent. These approaches result in a growing number of identified Vs that need to be classified. The goals of this study, apart from identifying pathogenic and likely pathogenic Vs, were to identify uncertain significance Vs (VUS) and bring to discussion their uncertainties and impact on patients and family members. Methodology: BRCA1 and BRCA2 were analyzed in 207 patients mainly with HBOC/HCS, using TruSight® Cancer and MiSeq. Annotation was performed with Variant Interpreter, VEP, HSF, IGV, Alamut and Varsome. Vs were divided in 3 groups (G) according to allele frequency (AF) in population databases (G1:AF>5%, G2:1%≤AF≤5% and G3:AF<1%) and classified according to ACMG-AMP guidelines. Results: In BRCA1 and BRCA2, 45 and 96 Vs were detected, respectively. While in BRCA1 G3, we detected 6 pathogenic (P) Vs and 9 VUS, in BRCA2 G3, we found 9P Vs, 2 Likely Pathogenic (LP), and 15 VUS. We highlight that in G3, VUS were more frequent than P and LP Vs. Discussion: Among G3, 28% of BRCA1 and 25% of BRCA2 Vs were VUS. VUS give rise to difficulties related to management of patients and families. Functional studies of missense or putatively affecting splicing VUS are of major importance to assess their biopathologic impact, as some of them may be hypomorphic and reclassified as P/LP. Accordingly, some VUS may have impact in therapeutic decisions (e.g. PARPi) as well as in patient’s cancer-risk management protocols, including appropriate genetic counselling and VUS screening in selected family members. We predict that new challenges related to VUS will emerge.